Technical condition of pipeline systems in operation - Prodous Oleg; Shlychkov Dmitriy; Abrosimova Ivanna; Chelonenko Andrey (E3S Web of Conferences)
The technical state of the pipeline systems that are now in use for different purposes was examined through analytical and field tests. The results were correlated, and the causes that cause instability in the system's operation were determined. It is established that the depreciation rates for pipeline systems that are currently in use are average in nature, do not sufficiently distinguish between application areas, operating conditions, diameters, and the degree of aggressiveness of the medium, and provide very little information regarding the potential for using new materials. If the difficulties related to pipeline wear are connected to the effectiveness of new solutions (structures, materials), the expected service life of old pipes will be further reduced in contrast to the economic limit of technical wear. As a result, steel pipelines may only be used when no other suitable option exists and they are coated on the inside for protection.